The Impact Of Government Policies Intervention On Poverty Reduction In Nigeria - Bala, Yusuf Zaria (2023)
This thesis examines the impact of government policies as an intervention in poverty reduction in Nigeria. First, it examines the relationship between government expenditure on training, education and investment infrastructure on poverty headcount reduction using the time series Autoregressive Distributed Lag (ARDL) and data from 1980-2019 for 40 years. Second, it employs the quantile regression method to understand the median relationship between financial assistance/aid, short and long-term debt and the real exchange rate on poverty reduction. Hence, it analysis the effects of macroeconomic factors such as government intervention or policies on reducing poverty headcount. Third, it examines the role of trade openness, foreign investment inflows, inflation rate and financial assistance/aid on poverty reduction. Evidence that suffices from the time series data indicates a positive long and short-run impact on poverty reduction. Further, it reveals that a more significant part of the variation in government policy or intervention can explain the peculiarity in poverty headcount reduction. In particular, government training expenditure, investment infrastructure, and foreign investment inflows have homogeneity and positively impact poverty headcount reduction. At the same time, foreign debt negatively affects poverty headcount reduction in the short run. Also, the quantile median reveals a positive and negative relationship between financial assistance/aid and foreign debt in the short term and a positive and significant relationship between real exchange rates on poverty headcount reduction in the short and long time (fluctuation).